Central nervous system manifestations in COVID‐19 patients: A systematic review and meta‐analysis. Issue 5 (9th January 2021) - Nazari, Shahrzad; Azari Jafari, Amirhossein; Mirmoeeni, Seyyedmohammadsadeq; Sadeghian, Saeid; Heidari, Mohammad Eghbal; Sadeghian, Siavash; Assarzadegan, Farhad; Puormand, Seyed Mahmoud; Ebadi, Hamid; Fathi, Davood; Dalvand, Sahar
Abstract: Background: At the end of December 2019, a novel respiratory infection, initially reported in China, known as COVID‐19 initially reported in China, and later known as COVID‐19, led to a global pandemic. Despite many studies reporting respiratory infections as the primary manifestations of this illness, an increasing number of investigations have focused on the central nervous system (CNS) manifestations in COVID‐19. In this study, we aimed to evaluate the CNS presentations in COVID‐19 patients in an attempt to identify the common CNS features and provide a better overview to tackle this new pandemic. Methods: In this systematic review and meta‐analysis, we searched PubMed, Web of Science, Ovid, EMBASE, Scopus, and Google Scholar. Included studies were publications that reported the CNS features between 1 January 2020 and 20 April 2020. The data of selected studies were screened and extracted independently by four reviewers. Extracted data analyzed by using STATA statistical software. The study protocol registered with PROSPERO (CRD42020184456). Results: Of 2, 353 retrieved studies, we selected 64 studies with 11, 687 patients after screening. Most of the studies were conducted in China (58 studies). The most common CNS symptom of COVID‐19 was headache (8.69%, 95%CI: 6.76%–10.82%), dizziness (5.94%, 95%CI: 3.66%–8.22%), and impaired consciousness (1.90%, 95%CI: 1.0%–2.79%). Conclusions: The growing number of studies has reported COVID‐19, CNS presentations as remarkable manifestations that happen. Hence, understanding the CNS characteristics of COVID‐19 can help us for better diagnosis and ultimately prevention of worse outcomes. Abstract : The most common CNS symptom of COVID‐19 was headache (8.69%, 95%CI: 6.76%–10.82%), dizziness (5.94%, 95%CI: 3.66%–8.22%), and impaired consciousness (1.90%, 95%CI: 1.0%–2.79%). The growing number of studies has reported COVID‐19, CNS presentations as remarkable manifestations that happen. Hence, understanding the CNS characteristics of COVID‐19 can help us for better diagnosis and ultimately prevention of worse outcomes.